1989
DOI: 10.3171/jns.1989.70.5.0676
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with cisplatin and etoposide for malignant intracranial germ-cell tumors

Abstract: Antitumor activity against intracranial malignant teratoma by combination chemotherapy with cisplatin and etoposide was evaluated in experimental and clinical studies. A human teratoma cell line (Tera 2) was exposed in vitro to cisplatin and/or etoposide, after which cell growth inhibition and alterations of deoxyribonucleic acid (DNA) histograms were observed. The results indicated that a synergistic cytotoxic effect was achieved by use of both agents in combination. Four cases of recurrent intracranial germ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 12 publications
1
36
0
3
Order By: Relevance
“…The radio-resistance of non-germinomatous germ cells in nature has led to the use of combination chemotherapy [8,[17][18][19][20]. Although long-term follow-up studies have not sufficiently been made, excellent response rates have been reported when cisplaitin and etoposide were given to 12 patients with newly diagnosed or recurrent germ cell tumors, suggesting that this chemotherapy is successful in the treatment of both geninoma and non-germinatous germ cell tumors [12]. However, the effects of this chemotherapy on pre-existing hormonal abnormalities were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The radio-resistance of non-germinomatous germ cells in nature has led to the use of combination chemotherapy [8,[17][18][19][20]. Although long-term follow-up studies have not sufficiently been made, excellent response rates have been reported when cisplaitin and etoposide were given to 12 patients with newly diagnosed or recurrent germ cell tumors, suggesting that this chemotherapy is successful in the treatment of both geninoma and non-germinatous germ cell tumors [12]. However, the effects of this chemotherapy on pre-existing hormonal abnormalities were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…We used CBDCA to reduce the nephrotoxicity of cisplatin. Etoposide, which was reported to be effective in treating malignant tumors [12,24], was combined with CBDCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in new and relapsed patients found responses and/or improved survival after platinum-containing regimens [17][18][19][20][21][22][23][24][25], with one study suggesting synergy with etoposide [26]. Alkylating agents, such as cyclophosphamide (CPM) also were added with apparent efficacy in some trials [12,14,23].…”
Section: Introductionmentioning
confidence: 99%
“…Using systemic chemotherapy, promising response rates have been achieved in newly diagnosed and relapsing patients with cyclophosphamide (Allen et al, 1987) or cisplatin-based regimens (Kobayashi, 1989;Patel et al, 1992). Consequently, new treatment strategies have been developed to use primary chemotherapy to avoid or to reduce radiotherapy in good responders.…”
mentioning
confidence: 99%